L'archeologia del graphic novel Il romanzo al naturale e l'effetto Töpffer - Brandigi, Eleonora (Premio Ricerca «Città di Firenze», 2013)
The archaeology of the graphic novel does not shed light on the historical origins of the comic book; on the contrary, it tries to discover the conceptual genesis of this narrative form. If the research methodology is archaeological, in fact, the theoretical approach is the same as neuro-narratology, in the light of which four important stages are suggested. These stages define the comic novel as a "natural" literary genre, a mimesis of the process transposing reality into images and constituting the basis of thought. The figure of Rodolphe Töpffer is not excluded from this process. Thanks to his theories and his work, he leads us to hypothesize that the comic book was more "novelistic" at its origin than it is in its current forms: the path to the novel, then, would not be so much of an evolution, but rather a return to the origins.